Novel Adenovirus Vectors ‘Capsid-Displaying’ a Human Complement Inhibitor - Seregin, Sergey S. (S. Karger AG, 2010)
Adenovirus (Ad) vectors are currently the most commonly utilized gene transfer vectors in humans worldwide. Unfortunately, upon contact with the circulatory system, Ads induce several, innate, complement-dependent toxicities that limit the full potential for Ad-based gene transfer applications. Therefore, we have constructed several novel Ad5-based vectors, ‘capsid-displaying’ as fiber or pIX fusion proteins, a complement-regulatory peptide (COMPinh). These novel Ads dramatically minimize Ad-dependent activation of the human and non-human primate complement systems, as determined by several assays. In summary, our work has shown that a novel COMPinh-displaying Ad5 has the potential for broadening the safe use of Ad vectors in future human applications.